An Inherited Balanced Translocation Between Chromosomes 4 and 6 in Recurrent Pregnancy Loss: A Case Report - Avvari, Srilekha; Akka, Jyothy; Madireddi, Sujatha; Pratibha, Nallari; Ananthapur, Venkateshwari (Journal of Family Medicine, 2019)
Recurrent pregnancy loss is an important reproductive issue with a heterogeneous etiology where two or more consecutive abortions occur before 20 weeks of gestation. Approximately 15% of all clinically recognized pregnancies result in miscarriage with an incidence of 1 in 300 cases. Couples, who experience repeated pregnancy loss before three months of gestation, mostly have fetuses with chromosomal aneuploids. A non-consanguineous couple with a married life of 4 years was referred to the Institute with a clinical history of three first trimester abortions. Karyotype analysis revealed a balanced autosomal translocation between chromosomes 4 and 6 with 46, XX, t (4;6)(q35; q22) karyotype in the female and normal 46, XY in the male partner. Therefore, the siblings and the couple were suggested for extended genetic counseling. Interestingly, similar translocation was seen in her father and three sisters, whereas her mother and elder sister showed a normal chromosomal constitution, indicating the paternal inheritance.
Keywords: Recurrent pregnancy loss; Karyotype; Balanced autosomal translocation; Unbalanced chromosomal rearrangement.